Simulation of extended reaction kinetics of palm oil-based polyol esters synthesis - Abd Hamid, Hamidah (2011)
The kinetics study on the synthesis of palm oil based polyol esters via transesterification between palm oil methyl esters (POME) and trimethylolpropane (TMP) has established that the reaction mechanism involves three stepwise reversible series-parallel elementary reactions. The first step of reversible monoesters esterification is suppressed by using excess POME and continual removal of methanol from the system while the other two steps are considered as reversible reactions. New kinetic modelling approach is needed in this field due to the limitation of the earlier kinetic models which had assumed complete irreversibility of all the reactions involved. The emphasis of this work is on the simulation of complex reaction kinetics via numerical method to determine the concentration-time profiles for various species involved in the transesterification reaction between POME with TMP in a batch reactor. The attention was focused on MATLAB® simulation due to its strong presence in the simulation field and its user-friendly factors. This research was also conducted to compare the available kinetic model via analytical solution with the new kinetic model via numerical method In this work, the rate equations from the previous study were extended and derived in terms of molar concentration and weight fraction-based equations. The weight fraction-based differential equations were then used as the reference for the program coding to simulate products distribution data values. In order to determine the rate constants for this kinetic model, the location of maximum local points and the final equilibrium of diesters and monoesters concentrations were considered in this study, while analyzing them statistically. The synthesis of palm oil methyl esters with trimethylolpropane was also done in a batch reactor to collect the reaction samples for certain period and then analyze them using gas chromatography system. The proposed models were verified by comparing with the data obtained from the experimental study and also with the published data available. In general, the results from the simulation of product distributions fitted well with the experimental data. However, there was a small deviation in the experimental data which occurred at the intermediate part of the reaction due to the fluctuation in the reaction temperature. The activation energies of the reactions were between 26.3 to 28.4 kcal/mol. Statistical analysis showed that the proposed kinetic model has a good agreement with the experimental data points. The new simulation approach was found to describe experimental data values satisfactorily and the accuracy of the kinetic model had been improved and verified.